2013
DOI: 10.1016/j.actatropica.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug resistance related genes as candidate markers for treatment outcome prediction of cutaneous leishmaniasis in Brazil

Abstract: The great public health problem posed by leishmaniasis has substantially worsened in recent years by the emergence of clinical failure. In Brazil, the poor prognosis observed for patients infected by Leishmania braziliensis (Lb) or L. guyanensis (Lg) may be related to parasite drug resistance. In the present study, 19 Lb and 29 Lg isolates were obtained from infected patients with different treatment outcomes. Translated amino acid sequence polymorphisms from four described antimony resistance related genes (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…This approach raised new insights into how effector mechanisms may be regulated within the granuloma and revealed a useful tool to interpret how interventions may operate. For cutaneous leishmaniasis, the analysis of DNA sequence of L. braziliensis and L. guyanensis isolated from patients with different treatment outcomes identified polymorphisms related to drug resistance [ 92 ]. This study showed that genes related to drug resistance could be used to discriminate the two species of the subgenus L. Viannia and also could predict treatment failure.…”
Section: Systems Biology As a Tool To Develop Vaccines Against CL mentioning
confidence: 99%
“…This approach raised new insights into how effector mechanisms may be regulated within the granuloma and revealed a useful tool to interpret how interventions may operate. For cutaneous leishmaniasis, the analysis of DNA sequence of L. braziliensis and L. guyanensis isolated from patients with different treatment outcomes identified polymorphisms related to drug resistance [ 92 ]. This study showed that genes related to drug resistance could be used to discriminate the two species of the subgenus L. Viannia and also could predict treatment failure.…”
Section: Systems Biology As a Tool To Develop Vaccines Against CL mentioning
confidence: 99%
“…Results from our study and other studies 30,34,35 indicate that the L. (V.) braziliensis population endemic to the state of Rio de Janeiro presents a homogeneous genetic pattern with low variability, which could explain the favorable therapeutic response to MA observed in patients who were infected in this state. However, therapeutic response to antimonial drugs may vary in states other than Rio de Janeiro, where ATL may be caused by different Leishmania species or by an L. (V.) braziliensis subpopulation with a high genetic variability 6,8,50 . Despite this fact, the results of the current study confirmed the findings of previous studies performed at INI/Fiocruz that included patients from other Brazilian states, 10,20,23,33 and suggest that patients infected by L. (V.) braziliensis or other Leishmania species may respond to low-dose MA, regardless of their geographic origin in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The L . guyanensis AQP1 sequence GU368155.1 (strain MHOM/BR/1997/NMT-MAO 328P clone B) was used as an additional reference [ 81 ]. Alignment was performed with ClustalW2 and plotted using TEXshade [ 79 , 80 ].…”
Section: Supporting Informationmentioning
confidence: 99%